Level walking and ambulatory capacity in persons with incomplete spinal cord injury: relationship with muscle strength - Kim, C Maria (2004)
STUDY DESIGN: Prospective analysis of relationships. OBJECTIVES: 1) to quantify the relationship between individual lower extremity muscle strength and functional walking measures and 2) to determine whether a multiple regression model incorporating lower extremity muscle strength could predict the performance of functional walking measures in persons with incomplete spinal cord injury (ISCI) living in the community. SETTING: Tertiary rehabilitation centre. Vancouver, Canada. METHODS: 22 subjects with ISCI participated. The relationship between functional walking measures (gait speed, six-minute-walk distance, and ambulatory capacity) and muscle strength (manual tests of hip flexors/extensors/abductors, knee flexors/extensors, ankle dorsiflexors/plantarflexors, and great toe extensors) were measured by Pearson correlation and regression procedures. RESULTS: For both the more and less affected sides, hip flexors, hip extensors, and hip abductors produced the highest correlations with the 3 functional measures. The less affected hip flexor strength explained more than 50% of the variance in gait speed and six-minute-walk distance while the less affected hip extensor strength explained up to 64% of the variance in ambulatory capacity. For all 3 functional measures, the strength of the less affected limb was more important than that of the more affected limb. CONCLUSIONS: Lower extremity muscle strength, in particular that of hip flexors, hip extensors, and hip abductors, is an important determinant of functional walking performance.